Fighting monetary colonialism in francophone Africa: Samir Amin's contribution. Issue 167 (2nd January 2021) - Sylla, Ndongo Samba
ABSTRACT: This article discusses Samir Amin's intellectual and activist contribution to the political economy of decolonisation in sub-Saharan Africa. It focuses on his fight from 1969 to 1975 for the monetary sovereignty of West African countries using the CFA franc, a colonial currency that survived independence. Amin was an advisor to Niger's President Hamani Diori alongside whom he fought to end monetary colonialism. As an alternative to the CFA franc, Amin recommended an ambitious economic integration for the West Africa region based on mutually supportive national currencies. Although his proposal would meet opposition from France, Senegal and Côte d'Ivoire, his economic case against the CFA franc is still relevant. With regard to the ongoing protests against the CFA franc, it is important to recall a major teaching from Amin: although monetary autonomy is necessary for economic development in peripheral countries, without a delinking strategy its effects will be limited.